The complex interplay of variables in studying teacher education - Flores, Maria Assunção (2019)
[Excerpt] Becoming a teacher entails a complex process which occurs over time in different contexts. Teacher education (TE) plays a central role in it. Although TE has been subject to criticism in regard to its effectiveness in preparing high quality teachers, it does make a difference for quality teachers (Flores 2016). As such, it requires careful programme design, an elaborated view of the intended process of teacher learning, specific pedagogical approaches and an investment in the quality of staff members (Korthagen, Loughran, and Russell 2006). Thus, debates focusing on TE revolve around, amongst other features, its curriculum, its rationale and key components, and its impact on the education and professional learning of preservice teachers (e.g., Darling-Hammond and Lieberman 2012; Livingston and Flores 2017). While teacher education is not to be seen as the panacea to improve education, it certainly does play a role in educating teachers to deal with the increasing complexities of teaching and learning in schools and classrooms in the 21st century. Issues such as motivations for becoming a teacher, the place of reflection in learning to teach, the formation of the professional identity as a teacher, the value of teacher education, the role of teacher educators and the importance of international and comparative perspectives in investigating teacher education are but a few examples of the complex interplay of variables in studying teacher education. The papers included in this issue investigate and discuss these aspects of teacher education. [...]